Analysis of financial statements at PT. Akasha Wira International Tbk. 2019-2023 period using the index number method - Agustina R.T Sitompul; Debora Anjey Situmorang; Ibbie Falia; Dwi Saraswati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Analysis of the Financial Report of PT Akasha Wira International Tbk. Aims to Determine The Company's Financial Performance by Compared The Figures in Its Financial Report. Want to see Whether the Company is getting better or noT over time. To do this analysis. Using The Index Number Method. This Method Compares Financial Figures in a particular year with the Previous Year. The Results Show That The Financial Performance of PT Akasha Wira Is Quite Fluctuating. Specifically, the cOompany's Profit Experienced The Largest Increase in 2018, which was IDR 417,281,000 OR 25.89% indicating a significant increase in income. Liabilities and Equity Experienced The Largest Increase in 2023 of IDR 2,262,899 OR 36.00%, Indicating An Increase InThe Company's Total Assets. This Could Indicate A Business Expansion OR Investment Made. Over a 5-year period, The Company Has Shown Sustainable Growth and Effective Utilization of Equity Resources.